1950
DOI: 10.1002/recl.19500690607
|View full text |Cite
|
Sign up to set email alerts
|

The Raman spectra of di‐, tri‐ and tetrathionate ions in aqueous solutions

Abstract: Frequency shifts and depolarization factors for the Raman lines of the S2O6“ion in aqueous solution are given. Three p and three dp lines are found. This proves ‐ in agreement with a conclusion drawn already by Duval and Lecomte from other evidence ‐, that the S2O6″ion has the staggered ethane‐like configuration with symmetry D3d. A few calculations for this ion are communicated. The Raman spectra of S3O6″ and S4O6″ in aqueous solution are determined. Incomplete polarization measurements for the Raman lines of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

1950
1950
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…The reaction schemes of the S 2 O 3 2– + O 3 reaction and the secondary chemistry in neutral aqueous phase are expected as those listed in Table . ,, Figure shows the representative Raman spectra of single aqueous STS microdroplets exposed to O 3 at two distinct RHs. The observed molecular Raman bands prior reaction can be solely assigned to the reactant S 2 O 3 2– . , When comparing the observed molecular Raman bands after reaction with those of several potential products from literature, Figure S1 shows that identifying SO 4 2– (reaction R1a), S 4 O 6 2– (reaction R1b), and S 3 O 6 2– (reaction R6) as the main products can lead to a good agreement with the observed Raman spectra after reaction. Such assignment agrees with the previous study of Okabe et al, where these three species mentioned above were reported as the final products of the STS + O 3 reaction in a neutral solution.…”
Section: Results Discussionsupporting
confidence: 67%
“…The reaction schemes of the S 2 O 3 2– + O 3 reaction and the secondary chemistry in neutral aqueous phase are expected as those listed in Table . ,, Figure shows the representative Raman spectra of single aqueous STS microdroplets exposed to O 3 at two distinct RHs. The observed molecular Raman bands prior reaction can be solely assigned to the reactant S 2 O 3 2– . , When comparing the observed molecular Raman bands after reaction with those of several potential products from literature, Figure S1 shows that identifying SO 4 2– (reaction R1a), S 4 O 6 2– (reaction R1b), and S 3 O 6 2– (reaction R6) as the main products can lead to a good agreement with the observed Raman spectra after reaction. Such assignment agrees with the previous study of Okabe et al, where these three species mentioned above were reported as the final products of the STS + O 3 reaction in a neutral solution.…”
Section: Results Discussionsupporting
confidence: 67%
“…marine isolates from deep sea environments (3000–4000 m depth). On the one hand, results slightly differ since Tuttle and Jannasch (1976) performed their experiments over longer periods of time ranging between 22 and 208 days at very low temperature 0–2°C and their expected oxidized product was polythionate and chiefly tetrathionate, definitely lacking in the present experiments (Gerding and Eriks, 1950). On the other hand, at 25°C and ambient pressure Thiobacillus sp .…”
Section: Resultscontrasting
confidence: 64%
“…The structure as given by Foss (1964),226 involves in addition to rlf the length of the central S-S bridge, and r2, the S-0 distance, also the 03S-S distances of 0.2116 nm, and the following angles: S-S-S 103.8°, O-S-O 113.6°, and S-S-0 107.9°, on the average. The set of vibration frequencies is incomplete, of the 24 values expected only 20 discrete ones are available when the data of Eucken (1948), 227 Gerding (1950), 228 Siebert (1955),81 Lecomte (1963) ,229 and Meyer (1980) and 148 cm-1.) These include assignments for six S-0 stretching frequencies, one for the S-S stretching frequencies (two more are needed), and seven of the bending and deformation mode frequencies (eight more are needed).…”
Section: F Ions Of the Type X2y" (N > 4)mentioning
confidence: 99%